DIFFERENTIATION OF RETINAL ASTROCYTIC HAMARTOMA FROM OTHER RETINAL NEOPLASMS: A CASE REPORT - A. S. Olshanskaya; N. A. Shnayder; D. V. Dmitrienko; O. Yu. Тruneva; E. V. Kozina; S. N. Lanin; S. S. Ilyenkov; Yu. A. Dykhno (Сибирский онкологический журнал, 2017)
Astrocytic retinal hamartoma (phacoma, astrocytoma) is a benign tumor, formed through proliferation of glial astrocytes and blood vessels of the sensory part of the retina. For the first time, eye involvement in tuberous sclerosis (TS) was described by J. van der Hoeva, Dutch ophthalmologist in 1921. A characteristic glial tumor is still considered a classic manifestation of this disease, however, retinal astrocytoma can be observed in practically healthy young people or children. We present the case of a 19-year-old woman diagnosed with multiple retinal hamartomas in the right eye. In addition to ophthalmoscopy, we used the additional diagnostic methods to determine the form of hamartomas (calcined or uncalcined) and differentiate astrocytic retinal hamartoma from other tumors of the retina and choroid as well as to exclude pathological changes in the central nervous system.